Approaches to improvement of treatment results of malignant tumors in adolescents and young adults - A. G. Rumyantsev; V. V. Ptushkin; S. V. Semochkin (Онкогематология)
This article provides an overview of clinical and biological features of most common malignant tumors in adolescents and young adults. The most effective pediatric and oncological treatment approaches to described diseases based on own experience are summarized.